As formações neológicas mais frequentes em comentários online: contribuições para o ensino do português - Matheus Henrique Duarte (2019)
The present research assumes the commitment to undertake a research about perspectives for the study of the lexicon, considering the most frequent neological formations in the emerging genre online commentary textual. Considering the impacts of the new digital technologies in the forms of the normalized use of the language, this work intends to describe the neological formations with their rules of word formation, present in online comments texts in virtual environments, as well as to inventory occurrences of lexical items present in online comments that present different formative processes of the presuppositions presented by the normative grammar and codify the procedures used in the formation of these words. In addition, the work also points to the need to present a pedagogical approach, based on the analysis of the neologisms collected, with emphasis on the teaching of the processes of formation of new words, this is because it is necessary to see that the teaching of Portuguese Language as we currently see, is rethought in a way that language teaching plays a significant role in the life of the student subject, since these impacts on the forms of language use have led to focus that directly affect the way of reading and writing and reconstruct institutionalized forms in order to propose new parameters for communication. According to Ferraz (2008, p. 146), the research defines “the open set, organized by productive rules, of the lexical units that make up the language of a linguistic community” and, in this context, the neological formations are classified according to Alves (1990) who define them as: semantic, formal and loan. Still in this direction, we also anchor ourselves in theorists such as Rocha (1998), Ganan¸ca (2017), Contiero and Ferraz (2014), Alves (2010), Valente (2010), Correia (2011), among others that deal with the neology in Brazilian Portuguese. In order to collect the data, we adopt as a methodological procedure the lexicographic criterion, in which it is only possible to affirm the neological character of the lexical item if it is not present in the dictionaries. To date, the data have revealed how language can present varied processes, not only those of grammar, to form new vocabulary that expresses greater expressiveness to speech, or even to name objects, events, among others. It is possible to perceive in the presented data the formations that are most common in the language and that, even, are present in the textbooks and are taught in the schools. As is the case of prefixal and suffix derivations that are still extremely productive in Brazilian Portuguese and also add a semantic value based on the intentionality of the user of the language.